Identificação de genes de Pasteurella multocida expressos em pulmão de suínos através da captura seletiva de sequências transcritas (SCOTS) e DUAL RNAseq - Chitarra, Cristiane Silva (2017)
Pasteurella multocida is one of the most important pathogen that causes economic losses in the swine industry, causing pneumonia in swine. The pathogenesis of the disease is now well understood, although several virulence factors have already been identified such as lipopolysaccharide, capsule, fimbriae, adhesions, toxins and membrane proteins. Therefore, this study has the objective to understand the pathogenesis of P. multocida when infecting the lung by next generation sequencing, RNAseq and by SCOTS technic comparing the transcriptome of P. multocida cultivated in vitro and in vitro. This is the first report of the use of RNAseq and SCOTS to identify gene regulation in P. multocida using a pig infection model. Twenty-one genes where differential expressed by SCOTS technic, those genes were classified in the following cellular functions: cell wall, surface, regulator, membrane transport, metabolism and unknown. A total of 704 genes were detected in vitro experiment and 1422 genes were detected in vivo experiment by RNAseq. Of those 2126 genes, 237 where differential expressed using log2-fold change ≥1 and adjusted P value of ≤0.1. Analyzing all the transcripts functions, 117 were downregulated and 120 genes were upregulated in vivo. The differential expressed genes occurs in stress situations, iron capture, heat shock chaperon proteins and nitrogren regulation.